Hukum Waris Nasional; Perbandingan Antara Kewarisan Islam, Burgerlijk Wetboek, dan Hukum Waris Adat - Anton, Anton; Husnainah Sobirin, Dinda; Hanifah, Farah; Tauzirie, Muhammad Faridz; Fauziah, Fitria (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research is motivated by the fact that there are still people who do not understand the applicable inheritance rules, even though Muslims, as the majority in Indonesia, already have inheritance laws that have been regulated clearly and in detail, by determining the distribution of assets based on kinship, including male and female heirs with specific portions. The distribution process begins with the fulfillment of obligations towards the body of the owner of the assets (tirkah), debt repayment, and implementation of the will. These provisions are based on the explanation of the verses of the Qur’an, especially Surah An-Nisa, as well as the Hadith and interpretations of scholars. In addition, Islamic inheritance law has main principles, such as the principles of ijbari and bilateral, which ensure the distribution of inheritance according to sharia provisions and fairly. Differences in religion sometimes become an obstacle to inheritance in Islamic law. In Indonesia, there are three inheritance law systems that apply, namely using Islamic inheritance law, using customary law, and using the Burgerlijk Wetboek. Customary inheritance law follows local traditions, the burgerlijk wetboek has similarities with customary law, while with Islamic law it has many striking differences and does not consider religious aspects that provide equal rights for all heirs. The social implications of the division of inheritance between Muslims and non-Muslims include the potential for family conflict, relationship tension, and perceptions of injustice. Some solutions include wills or gifts, family deliberations, and inheritance law education to reduce conflict and ensure fair distribution. A harmonious approach through deliberation is often the choice to maintain harmonious family relationships and the conditions of a pluralistic society in Indonesia.